Evaluation and Identification of Opportunities for Saving Electrical Energy Consumption in Artificial Lighting Systems Inside Buildings (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
The artificial lighting system is a major component in a building, consuming up to 50% of its electrical energy. Hence, it is crucial to evaluate and identify opportunities for energy savings. Industries involve numerous operational instruments, one of which is building structures with artificial lighting systems. The requirements for artificial lighting systems consider energy conservation principles aimed at achieving energy consumption efficiency during operation. Therefore, a series of energy management activities and energy conservation evaluations are conducted through an audit of the artificial lighting system in a building with 50 rooms (the study object). The audit method used is the Short Energy Audit (SEA) to calculate Energy Consumption Intensity (ECI) under actual conditions (condition 1) and predictions under improvement conditions (condition 2). The results depict an energy usage portrait (evaluation) showing that 100% of electricity consumption is efficient, with the ECI target standard at 2,5 kWh/m2. The percentage saving (PS) in condition 1 are 68,058% and in condition 2 are 64,967%, indicating that improvements will not significantly alter the energy saving opportunities but will provide considerable benefits in operational investment. Recommendations include making small short-term investments in repairs, maintenance, optimizing lighting system operations, and conducting initial energy audits